Evaluation of Teacher Leadership Training Model Based on Competency From The Qur'an at Al Ittihadiyah Madrasah in North Sumatera - Syafaruddin Syafaruddin; Ramadan Lubis (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to analyze the evaluation of the competency-based teacher leadership training model from the Qur'an at Madrasah Al Ittihadiyah in North Sumatra. This study uses a qualitative approach with analytical descriptive method. The data collection techniques were carried out through interviews, observation and documentation. Furthermore, the data were analyzed through the stages of data reduction, data exposure, and drawing conclusions. To ensure the validity of the data, triangulation techniques (method triangulation and source triangulation) were used. The results of this study found (1) Context evaluation, that Al Ittihadiyah teachers did not receive professional teacher training program services due to the lack of budget for DPW and Al Ittihadiyah Madrasah North Sumatra. For this reason, the module is used as an alternative source of teacher leadership training materials; (2) Evaluation of inputs, including the training program implementation committee and the DPW Al Ittihadiyah North Sumatra for two days (as resource persons and facilitators), plus modules, books, and supporting references during the training; (3) Process evaluation, including the training process carried out in accordance with the plans and objectives, both administratively (services) and managerially; (4) Product evaluation, which is in the form of changing the teacher's perspective and accepting an integrated training model, changing the knowledge, attitudes and skills of teachers in leading competency-based learning from the Qur'an. These competencies are in the form of communication, opening lessons, explaining, providing reinforcement, closing learning, making decisions, and providing examples.